Nutcracker Syndrome—An Unusual Case of Chronic Left Upper Abdominal Pain: A Case Report. Issue 3 (1st February 2019) - Patel, Bimal; Samuel, Samuel
Abstract : A 38-year-old woman presented with a chief complaint of sharp, achy left upper abdominal pain with radiation to the left flank. This pain started approximately one-and-a-half years before she consulted with a pain specialist. Although an extensive workup was completed, no organic cause was established as the cause of her pain. After undergoing successful fluoroscopically guided celiac plexus blocks, an abdominal magnetic resonance imaging scan was obtained that revealed nutcracker phenomenon. The patient was evaluated by an urologist and underwent renal autotransplantation. The patient subsequently had complete relief of her pain.